Output Feedback Fuzzy Gain Scheduling for MIMO Systems Applied to Flexible Aircraft Control - Guilherme C. Barbosa; Flávio J. Silvestre (Aerospace, 2025)
Previous works by our group evidenced stability problems associated with flight control law design for flexible aircraft regarding gain scheduling. This paper proposes an output feedback fuzzy-based gain scheduling approach to adequate closed-loop response in a broader range of the flight envelope. This method applies a variation of the controller gains based on the membership function design for all the varying parameters, such as dynamic pressure. It aims for performance improvement while enforcing global stability gain scheduling. The technique was demonstrated for the flexible ITA X-HALE aircraft nonlinear model and compared to the classical interpolation-based gain scheduling technique. The results revealed that fuzzy-based gain scheduling can effectively handle high-order systems while ensuring global system stability, leading to an overall improvement in performance.